Politics, Power and a Pandemic: Searching for Information and Accountability During a Twitter Infodemic. (March 2022) - LaPoe, Benjamin R.; Carter Olson, Candi S.; LaPoe, Victoria L.; Jain, Parul; Woellert, Allyson; Long, Aaron
During the early weeks of the U.S. COVID-19 pandemic, society was battling an infodemic–defined as a "tsunami" of online misinformation. Through the lens of mediatization theory, this article examines 800, 000 tweets to understand social media information and misinformation related to the COVID-19. Through multi-layered analysis, this article details prominent key words discussed on Twitter connected to pandemic trending hashtags in early-to-mid March 2020: #Covid19 and #Coronavirus. The most prominent word themes included: novelty of this virus and associated uncertainty and the spread of misinformation; severity and widespread reach of the virus; call for collective action; and expectations relative to government action. The article explains these findings through mediatization theory, applying how technology influences social media discussions.